2012
DOI: 10.1074/jbc.m112.345082
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Alternative Pathway Complement Activation by Targeting the Factor D Exosite

Abstract: Background: Anti-factor D antibody blocks a rate-limiting step in the alternative complement pathway. Results: The structure of anti-factor D in complex with factor D provides the molecular basis of complement inhibition. Conclusion: Anti-factor D binds to the factor D exosite and inhibits alternative pathway complement activation. Significance: Targeting the exosite on proteases could have great potential for antibody therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 38 publications
1
64
0
Order By: Relevance
“…Antigen retrieval was done using pronase E digestion for 40 minutes at 37°C (C1q, C3c) or cooking for 2, 5 min in target retrieval solution pH 6 (DAKO Deutschland). After blocking of endogenous peroxidase using 3% H 2 O 2 and Avidin-Biotin block (Vector laboratories, Burlingame, CA, USA), normal goat serum and blotto (1:5) sections were incubated over night at 4°C using the following antibodies diluted in 1%BSA in 50 mM Tris pH 7, 4: C1q, a rabbit polyclonal antibody against human C1q (A0126; DAKO Deutschland, Hamburg, Germany); C3c, a rabbit polyclonal antibody against human C3c (A0062; DAKO Deutschland); C3d, a mouse monoclonal antibody against human C3d (Quidel, Athens, OH, USA); C9, a mouse monoclonal antibody against human C9 (Quidel, Athens, OH, USA); CFD, a mouse monoclonal antibody directed against active human complement factor D (Clone 8E2, provided by F. Hoffmann-La Roche Ltd, Basel, Switzerland [19]); MASP-2, a rabbit polyclonal directed against human Mannan-binding lectin serine peptidase 2 (Sigma Aldrich, Taufkirchen, Germany); Collectin-11, a rabbit polyclonal antibody against Collectin-11 (Sigma Aldrich). After washing with 50 mM Tris pH 7, 4, sections were incubated with biotinylated secondary goat anti-rabbit IgG (BA-1000; Vector laboratories) or horse anti-mouse IgG (BA-2001, Vector laboratories).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Antigen retrieval was done using pronase E digestion for 40 minutes at 37°C (C1q, C3c) or cooking for 2, 5 min in target retrieval solution pH 6 (DAKO Deutschland). After blocking of endogenous peroxidase using 3% H 2 O 2 and Avidin-Biotin block (Vector laboratories, Burlingame, CA, USA), normal goat serum and blotto (1:5) sections were incubated over night at 4°C using the following antibodies diluted in 1%BSA in 50 mM Tris pH 7, 4: C1q, a rabbit polyclonal antibody against human C1q (A0126; DAKO Deutschland, Hamburg, Germany); C3c, a rabbit polyclonal antibody against human C3c (A0062; DAKO Deutschland); C3d, a mouse monoclonal antibody against human C3d (Quidel, Athens, OH, USA); C9, a mouse monoclonal antibody against human C9 (Quidel, Athens, OH, USA); CFD, a mouse monoclonal antibody directed against active human complement factor D (Clone 8E2, provided by F. Hoffmann-La Roche Ltd, Basel, Switzerland [19]); MASP-2, a rabbit polyclonal directed against human Mannan-binding lectin serine peptidase 2 (Sigma Aldrich, Taufkirchen, Germany); Collectin-11, a rabbit polyclonal antibody against Collectin-11 (Sigma Aldrich). After washing with 50 mM Tris pH 7, 4, sections were incubated with biotinylated secondary goat anti-rabbit IgG (BA-1000; Vector laboratories) or horse anti-mouse IgG (BA-2001, Vector laboratories).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Genentech subsequently developed a humanized IgG murine anti-FD antibody (FCFD4514S) and showed that it could block the formation of the alternative pathway, C3 convertase [85]. The FD antibody was named lampalizumab.…”
Section: Complement As a Therapeutic Target In Amdmentioning
confidence: 99%
“…The earliest clues that controlling FD might affect retinal disease came from a mouse model where it was shown that photoreceptors were protected from light induced damage in FD knockout animals [84]. Based on these promising findings, Genentech, Inc. (San Francisco, CA) has developed a humanized IgG Fab murine anti-factor D antibody (FCFD4514S) [85]. In vitro studies showed that this monoclonal antibody blocked the FD mediated proteolytic activation of its C3bB substrate [85].…”
Section: Successful Targeting Of Factor D In Amd?mentioning
confidence: 99%